FAULT TREES AND BELIEF NETWORKS IN RISK MODELLING: A COMPARATIVE ANALYSIS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
Nowadays, an ever-growing complexity of technical systems can be observed worldwide, problems of rational use of nature resources and diminution in negative impact on the environment are not completely settled yet, and international competition in different areas is strengthening. All the above tendencies cause an increase of different risks: technical, ecological, political, military and financial. Due to their nature, most of the risks are caused by a set of factors with commonly unknown relationships. Therefore, the need to use risk modelling methods that enable visual representation of the sets of cause-risk relationships becomes evident. This paper briefly examines two widely used techniques of modelling risky situations: fault trees and belief networks, and provides their comparative analysis.